Light fidelity performance via hybrid free space optic/fiber optic communication under atmospheric disturbance - Satea Hikmat Alnajjar; Ahmed Majid Hameed (Institute of Advanced Engineering and Science, 2022)
Light f idelity (Li-Fi) considers technology in optical wireless communication (OWC) that utilize visible light for transmission in free space, visible light communication (VLC) technology was chosen to overcome the interference issues of radio frequency (RF) communication and it also has higher bandwidth and is more secure. This paper aims to analyse the influence of atmospheric attenuation on the end-users of VLC system that consisted of five light-emitting diodes (LEDs) distributed in a room, which in t urn linked with the hybrid optical system includes a multi-channel of free space optic (FSO) connected with a fiber-optic channel (FOC). The hybrid system to the end-user was estimated in terms of bit error rate, quality factor, and signal power under dust-rain weather conditions. In the dust scenario, the suggested system achieved acceptable bit-error-rate (BER) to a distance of 1, 100 m. In rainy conditions, the performance accomplished acceptable BER to a distance of 3000 m. The VLC system's end-user also was evaluated under the effectiveness of the variation of irradiance and incident angles. Despite the harsh environmental conditions imposed on the communication network, VLC has proven its ability to maintain acceptable performance in end-user.